Population, Family Planning and Reproductive Health Policy Harmonization in Bangladesh - El-Saharty, Sameh; Ahsan, Karar Zunaid; May, John F. (World Bank, Washington, DC, 2014)
Over the past 30 years, Bangladesh has achieved significant economic and human development progress, and demonstrated impressive policy as well as programmatic commitment to lowering the fertility level. However, its future socioeconomic prospects may be hampered by its population growth rate, depending on how quickly the fertility rates decline and at which point they stabilize. Projections estimate that the total population of Bangladesh in 2051 could increase to 218.1 million under a laissez faire projection scenario and 201.3 million under an accelerated fertility transition (AFT) scenario. This difference would have significant impacts on public spending, public services, and job creation. An AFT scenario would enable the country to improve the dependency ratios possibly resulting in economic benefits from harnessing the demographic dividend for several decades. To accelerate the demographic transition, the government will need to revitalize high-level coordination to ensure multisectoral engagement in population policies, including increasing the age at marriage, and improving education, skills development, job creation, and social safety nets for the vulnerable population groups. In addition, a sustained decline in fertility through increased access and coverage of family planning (FP) services is crucial, mainly by focusing on lagging regions and hard-to-reach areas, and by expanding the supply and provision of FP long acting and permanent methods. Strengthening the synergy and coordination of service delivery between the Health and FP directorates by building capacity for systems strengthening; promoting cross-referral between programs; and efficient provisioning of FP and reproductive health services through community clinics need to remain at the forefront of the government s health improvement efforts in Bangladesh.